2022
DOI: 10.1371/journal.pone.0268249
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in post-stroke cognitive decline: A population-based longitudinal study of nationally representative data

Abstract: Background Sex differences in post-stroke cognitive decline have not been systematically evaluated in a nationally representative cohort. We use a quasi-experimental design to investigate sex differences in rate of post-stroke cognitive decline. Methods Utilizing the event study design, we use the Health and Retirement Study (HRS) data (1996–2016) to evaluate the differences (percentage points [95% Confidence interval]) in the rate of change in cognitive function, measured using the modified version of the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Cerebral SVD burden has been strongly associated with post-stroke cognitive and functional outcomes ( 44 , 45 ). Most studies have been focusing on the early post-stroke period but also indicating that women more frequently than men experienced cognitive deficits ( 16 ). In the Health and Retirement Study, Bako et al detected a significant short-term acceleration of cognitive decline for the overall population (4.2 percentage points) and among female participants (5.0 percentage points), but no evidence of long-term acceleration of the cognitive decline after stroke was noted ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerebral SVD burden has been strongly associated with post-stroke cognitive and functional outcomes ( 44 , 45 ). Most studies have been focusing on the early post-stroke period but also indicating that women more frequently than men experienced cognitive deficits ( 16 ). In the Health and Retirement Study, Bako et al detected a significant short-term acceleration of cognitive decline for the overall population (4.2 percentage points) and among female participants (5.0 percentage points), but no evidence of long-term acceleration of the cognitive decline after stroke was noted ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have been focusing on the early post-stroke period but also indicating that women more frequently than men experienced cognitive deficits ( 16 ). In the Health and Retirement Study, Bako et al detected a significant short-term acceleration of cognitive decline for the overall population (4.2 percentage points) and among female participants (5.0 percentage points), but no evidence of long-term acceleration of the cognitive decline after stroke was noted ( 16 ). We found a significant association between medium-to-long-term CI and the female sex, which is in accordance with studies reporting female sex was an independent predictor of post-stroke CI ( 13 15 ), although there are conflicting results as well ( 46 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent cohort study of community-dwelling adults in the US found that women experience more post-stroke cognitive deficits even after controlling for pre-stroke cognitive measures, particularly during the early post-stroke period. 131…”
Section: Lifetime Endogenous Estrogen Exposurementioning
confidence: 99%
“…The differences were fully attenuated after adjustment for covariates, indicating that the major contributing factors to the worse post-stroke cognitive outcomes in women were a higher prevalence of being widowed, older age at stroke onset, worse pre-stroke functional and cognitive status, and lower educational attainment. Another recent cohort study of community-dwelling adults in the US found that women experience more post-stroke cognitive deficits even after controlling for pre-stroke cognitive measures, particularly during the early post-stroke period [ 131 ].…”
Section: Stroke Outcomes ( Figure 3 )mentioning
confidence: 99%